Inorganic chemistry - Miessler, Gary L.; Tarr, Donald A. (Delhi: Pearson Education, 2009)
This highly readable text provides the essentials of Inorganic Chemistry at a level that is neither too high (for novice students) nor too low (for advanced students). It has been praised for its coverage of theoretical inorganic chemistry. It discusses molecular symmetry earlier than other texts and builds on this foundation in later chapters. Plenty of supporting book references encourage instructors and students to further explore topics of interest.
Appendices 671-729p.; Index 730-740p.
Keywords: Inorganic chemistry; Chemistry